Problematika Pengembangan Kurikulum Dan Pembelajaran Pendidikan Agama Islam (PAI) (Studi kasus di MA Huffadh Al-Itqoniyyah Bobotsari Kabupaten Purbalingga) - Muhammad Nur Rizal1; Budi wijaya (ISLAMISCHE BILDUNG: Jurnal Pendidikan Agama Islam, 2024)
Abstract: This research aims to describe the problems and strategies for developing PAI curriculum and learning at MA Huffadh Al-Itqoniyyah Bobotsari, Purbalingga Regency. The main questions to be answered through this research are: First, what are the problems of curriculum development and PAI learning at MA Huffadh Al-Itqoniyyah Bobotsari, Purbalingga Regency. Second, what are the problems and strategies in overcoming the problems of curriculum development and PAI learning at MA Huffadh Al-Itqoniyyah Bobotsari, Purbalingga Regency.This research uses qualitative research with data collection techniques using observation methods, interview methods. The research subject was the head of the MA Huffadh Al-Itqoniyyah Bobotsari madarasah, Purbalingga Regency.The results of this research are first, the problem of curriculum development and PAI learning, namely the lack of educator participation in curriculum development and PAI learning is focused on the classroom; policies from national education, Islamic boarding schools and Ma'arif educational institutions which sometimes hinder the development of curriculum in madarasahs; addition of subjects that cause material to overlap; lack of synergy between madarasas and families; lack of empowerment of learning resources and evaluation which still focuses on cognitive aspects. Second, the strategy for overcoming the problems of PAI curriculum development and learning is to improve the quality of educators by involving them in curriculum development and training that increases educator competency; reviewing and integrating policies from national education, Islamic boarding schools and Ma'arif educational institutions to become madarasah policies and madarasah programs; home visits for students who have problems at madarasah as well as communication with student guardians.